2021
DOI: 10.1021/acsami.0c20724
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and Storage Mechanisms for Nitrogen Oxides on Variously Terminated (001) Surfaces of SrFeO3−δ and Sr3Fe2O7−δ Perovskites

Abstract: The Ruddlesden–Popper (RP)-type layered perovskite is a candidate material for a new nitrogen oxide (NO x ) storage catalyst. Here, we investigate the adsorption and oxidation of NO x on the (001) surfaces of RP-type oxide Sr3Fe2O7−δ for all of the terminations by comparing to those of simple perovskite SrFeO3−δ by the density functional theory (DFT) calculations. The possible (001) cleavages of Sr3Fe2O7 generate two FeO2- and three SrO-terminated surfaces, and the calculated surface energies indicated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…73 The absorption peak at 1304 cm −1 was attributed to HNO 3 . 70 The above results were consistent with formulas (1)- (8).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…73 The absorption peak at 1304 cm −1 was attributed to HNO 3 . 70 The above results were consistent with formulas (1)- (8).…”
supporting
confidence: 72%
“…NO + ˙OH → HNO 2 (7) NO 2 + ˙OH → HNO 3 (8) Weak photocatalytic activity always induces the generation of NO 2 , which is due to the incomplete oxidation of NO. Since NO 2 is more toxic than NO and leads to greater damage to the environment, the production of NO 2 should be minimized when NO is oxidized to NO x .…”
Section: Environmental Science: Nano Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The disappearance of the IR absorptions at approximately 473 K indicated that the large desorption peak at low temperatures observed in the NO x desorption profile of the Mn-doped catalyst (Figure ) was from the bridging nitrate and nitro species. Generally, basic sites such as the Ba sites in Pt/Ba/Al 2 O 3 and Sr sites in Sr–Fe perovskites can easily adsorb NO x species. ,, Both bidentate nitrate and free surface nitrite ions were observed on all the examined catalysts, suggesting that these species must be adsorbed on the Sr sites. However, bridging nitrate and nitro species at 1623 and 1393 cm –1 , respectively, were observed in the Mn-doped catalysts and SrTiO 3 in the DRIFT spectra of the NO x species adsorbed on SrTi 1– x Mn x O 3 (Figure S7), suggesting that the Mn or Ti sites act as the adsorption sites.…”
Section: Resultsmentioning
confidence: 91%
“…29 Generally, the efficiency of N 2 fixation in the NTP can be improved by using a catalyst. 30−32 Perovskites are used in various reactions, 33−36 especially for oxidation reactions such as the oxidation of nitrogen oxide 35,37,38 and carbon monoxide, 39,40 because of their excellent thermal stability, electronic structure, ionic conductivity, electron mobility, and redox behavior.…”
Section: Introductionmentioning
confidence: 99%